2007
DOI: 10.1149/1.2400602
|View full text |Cite
|
Sign up to set email alerts
|

Microemulsion Synthesized Pt∕Ru∕Sn Nanoparticles on BDD for Alcohol Electro-oxidation

Abstract: Ternary Pt-based nanoparticles ͑nominal composition Pt 80 Ru 10 Sn 10 ͒ were synthesized via the microemulsion route and deposited onto boron-doped diamond ͑BDD͒ electrode. The particle size measured by transmission electron microscopy was in the 2-5 nm diam range. X-ray photoelectron spectroscopy revealed a slightly different surface composition from that of the bulk and showed no chemical shift of the Pt 4f 7/2 line in ternary Pt/Ru/Sn nanoparticles. For both methanol and ethanol electro-oxidation, the terna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 33 publications
1
33
0
Order By: Relevance
“…The increase in Sn content clearly resulted in a serious Ru depletion in the catalyst compared to the nominal composition. Sine et al [33] observed a similar Ru depletion on the surface of a PtRuSn ternary catalyst based on an XPS study, which was explained as Ru being repelled from the catalyst surface by Sn. For the commercial catalyst, PtRu HISPEC5000, a good agreement is shown between the actual and nominal composition.…”
Section: Defc Single-cell Characterizationmentioning
confidence: 81%
See 3 more Smart Citations
“…The increase in Sn content clearly resulted in a serious Ru depletion in the catalyst compared to the nominal composition. Sine et al [33] observed a similar Ru depletion on the surface of a PtRuSn ternary catalyst based on an XPS study, which was explained as Ru being repelled from the catalyst surface by Sn. For the commercial catalyst, PtRu HISPEC5000, a good agreement is shown between the actual and nominal composition.…”
Section: Defc Single-cell Characterizationmentioning
confidence: 81%
“…9a and b showing polarization curves recorded after the durability test normalized to the MEA surface area and platinum loading, respectively. The maximum power density of commercial Pt 83 Sn 17 33 /C showed a maximum power density loss of 52, 64 and 67%, respectively. At this stage, it is difficult to draw meaningful conclusions around this behavior because more post-durability investigations are needed regarding the catalyst composition, reaction products analysis, MEA diagnostics and more.…”
Section: Defc Durability Testmentioning
confidence: 96%
See 2 more Smart Citations
“…(4)) [82]. Cathodic catalysts to be used in fuel cells are also reported to be synthesized via microemulsion route [83]. Yet, the microemulsion-synthesized nanocatalysts exhibit unsatisfactory long-term stability [84]:…”
Section: Electrocatalysismentioning
confidence: 99%